Cost effectiveness analysis of minimally invasive internal thoracic artery bypass versus percutaneous revascularisation for isolated lesions of the left anterior descending artery. Issue 7594 (2nd March 2007) - Rao, Christopher; Aziz, Omer; Panesar, Sukhmeet Singh; Jones, Catherine; Morris, Stephen; Darzi, Ara; Athanasiou, Thanos
Abstract : Objective To compare the cost effectiveness of percutaneous transluminal coronary artery stenting with minimally invasive internal thoracic artery bypass for isolated lesions of the left anterior descending artery. Design Cost effectiveness analysis. Data sources Embase, Medline, Cochrane, Google Scholar, and Health Technology Assessment databases (1966-2005), and reference sources for utility values and economical variables. Methods Decision analytical modelling and Markov simulation were used to model medium and long term costs, quality of life, and cost effectiveness after either intervention using data from referenced sources. Probabilistic sensitivity and alternative analyses were used to investigate the effect of uncertainty about the value of model variables and model structure. Results Stenting was the dominant strategy in the first two years, being both more effective and less costly than bypass surgery. In the third year bypass surgery still remained more expensive but became marginally more effective. As the incremental cost effectiveness was £1 108 130.40 (€1 682 146.00; $2 179 194) per quality adjusted life year (QALY), the additional effectiveness could not be said to justify the additional cost at this stage. By five years, however, the incremental cost effectiveness ratio of £28 042.95 per QALY began to compare favourably with other interventions. At 10 years the additional effectiveness of 0.132 QALYs (range −0.166 to 0.430) probably justified the additional cost of £829.02 (range £205.56 to £1452.48), with an incremental cost effectiveness of £6274.02 per QALY. Sensitivity and alternative analysis showed the results were sensitive to the time horizon and stent type. Conclusions Minimally invasive left internal thoracic artery bypass may be a more cost effective medium and long term alternative to percutaneous transluminal coronary artery stenting.